The impact of technology in history and archaeology - Woolf, Alex (Chicago, Illinois Heinemann Raintree, 2016)
"How have technology and science helped historians and archaeologists through the years? How does today's technology help us understand the past? What role does technology hold for the future of history studies? From the invention of metal detectors through to today's computer modeling of long-dead people, our knowledge of the past has always been improving thanks to technology. This book looks at historical
A gift from book Africa
Science
This edition in Paperback
1 2 13 15
NEW_ZTN_GN
Keywords: Archaeology -- Methodology -- Juvenile literature; Archaeology -- Technological innovations -- Juvenile literature; History -- Technological innovations -- Juvenile literature